Analisis Metode Open Web Application Security Project (OWASP) Menggunakan Penetration Testing pada Keamanan Website Absensi - Ichsan Octama Riandhanu (Jurnal Informasi dan Teknologi, 2022)
The use of technology in various fields increases mobility, one of which is the creation of websites to share and manage information. Information system security that cannot interfere with the infrastructure of an organization or company. Many system vulnerabilities or system problems occur on the internet. These problems can be in the form of Malware attacks, Exploits and Injection databases. This problem can be minimized by implementing security from hackers' interference or attacks by means of penetration testing (Pentest), which is testing carried out on the web legally by imitating the form of hackers. To detect web security, an analysis of the vulnerabilities of a web is required in accordance with the security standardization of the Open Web Application Security Project (OWASP) using security tools. Web-based vulnerability analysis with the OWASP method using security tools is able to determine the security level of an application, based on the results of tests that have been carried out where the results of the research provide some suggestions or recommendations about website vulnerabilities, which can be used by the website development team to improve website security.